Calculi in the Prostatic Surgical Bed as a complication after Holmium Laser Enucleation of the Prostate - Lee, Young Ju; Oh, Seung-June (Urology Journal, 2018)
Purpose: To report de novo calculi in the prostatic surgical bed as a complication of Holmium laser enucleation of the prostate (HoLEP). Materials and Methods: Patients who underwent HoLEP and were enrolled in our Benign Prostatic Hyperplasia (BPH) Database Registry from July 2008 to December 2015 were reviewed. Cases of calculi removal in the prostatic surgical bed were identified. Clinical data, including preoperative evaluation, postoperative symptoms with a detailed history, urinalysis, pathology, cystourethroscopy, and stone analysis were collected and described. Results: Eight patients were identified including one patient who underwent HoLEP at another hospital. Among the 877 patients in our BPH database, 7 (0.8%) underwent calculi removal in the prostatic surgical bed. Median age was 67.0 years. Median prostatic volume was 75.5mL. The most common symptom was severe stabbing urethral pain (n = 4), with a median of 13 months after HoLEP. Calculi were pedunculated in the prostatic surgical bed or in the bladder neck with a small mucosal connection. Pathology of the resected tissue showed granulation tissue formation and dystrophic calcification. Conclusion: Calculi in the prostatic surgical bed or the bladder neck after HoLEP have never been reported previously. Although it is very rare, recurrent urethral pain, persistent pyuria, and recurrent gross haematuria are signs for further investigation. Cystourethroscopy should be performed to rule out the presence of stones. Careful history taking and having an index of suspicion are important for the diagnosis.